SME Registration Evidence from a Randomized Controlled Trial in Bangladesh - De Giorgi, Giacomo; Rahman, Aminur (World Bank, Washington, DC, 2013)
Informality is pervasive in developing countries. In Bangladesh, the majority of firms are informal and as such they might not have access to prime markets, while lowering the tax base. The authors implemented an information campaign on registration, including both the step-by-step procedures and the potential benefits from registration. They find that the treatment made firms more aware of the procedures, but had no impact on actual registration. The results point toward potentially low benefits and high indirect costs of registration as the main barriers to formality (e.g. access to markets, taxation, labor and product regulations).